FEATURES OF THE CREATION AND DEVELOPMENT OF QUALITY MANAGEMENT SYSTEMS FOUNDRIES - V. M. Yarkovich (Литьë и металлургия)
The report reveals the most difficult questions of a quality management system of casting processes creation.